Occurrence of fresh water jelly-fish, Limnocnida indica (Annadale) in Hemavathi reservoir and its limnological perspective - Manna, R K; Das, A K; Sigh, D N; Khan, M Feroz (Indian Journal of Fisheries, 2011)
Occurrence of the freshwater medusa, Limnocnida indica in Hemavathi reservoir, Karnataka, India has been observed during February-March, 2002. Like their occurrence they in disappeared suddenly from April, 2002. They reappeared in the same place at the same period during 2003 and 2004. A critical environmental balance seems to play a key role in their conversion from polyp to medusae form. Hence, limno-chemical and plankton data of the reservoir are given to understand the suitable habitat for their growth